2020
DOI: 10.1200/cci.19.00114
|View full text |Cite
|
Sign up to set email alerts
|

Workflow Differences Affect Data Accuracy in Oncologic EHRs: A First Step Toward Detangling the Diagnosis Data Babel

Abstract: PURPOSE Diagnosis (DX) information is key to clinical data reuse, yet accessible structured DX data often lack accuracy. Previous research hints at workflow differences in cancer DX entry, but their link to clinical data quality is unclear. We hypothesized that there is a statistically significant relationship between workflow-describing variables and DX data quality. METHODS We extracted DX data from encounter and order tables within our electronic health records (EHRs) for a cohort of patients with confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…We did not evaluate data quality, but other studies have demonstrated that both the clinical workflows and the clinical stakeholders involved in generating EHR data impact clinical data availability and quality. 11 Optimally designed…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not evaluate data quality, but other studies have demonstrated that both the clinical workflows and the clinical stakeholders involved in generating EHR data impact clinical data availability and quality. 11 Optimally designed…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate data quality, but other studies have demonstrated that both the clinical workflows and the clinical stakeholders involved in generating EHR data impact clinical data availability and quality. 11 Optimally designed workflows in the EHR are central for improving HCP efficiency and reducing HCP burnout, but unfortunately in the transition from paper records to the EHR, most health systems simply replicated their tools and workflows from paper, constructing the “note” as the artifact of focus for the HCP. A redesign of local workflows with change management is needed to pivot HCPs from the old “note-centric” approach to the EHR, to a more data-oriented approach.…”
Section: Discussionmentioning
confidence: 99%
“…26 For example, variations in the quality of diagnosis coding for brain neoplasms have been demonstrated to correlate with workflow, care setting, and personnel. 27 Resolution of these challenges requires the use of emerging systems to provide monitoring of EHR data for data quality issues 28 , 29 and the inclusion of data quality considerations during EHR system implementations.…”
Section: Discussionmentioning
confidence: 99%